2012
DOI: 10.1021/la300108f
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Transitions Triggered by Specific Binding of Vesicles to Protein-Decorated Interfaces of Thermotropic Liquid Crystals

Abstract: We report that specific binding of ligand-functionalized (biotinylated) phospholipid vesicles (diameter = 120 ± 19 nm) to a monolayer of proteins (streptavidin or anti-biotin antibody) adsorbed at an interface between an aqueous phase and an immiscible film of a thermotropic liquid crystal (LC) (nematic 4′-pentyl-4-cyanobiphenyl (5CB)) triggers a continuous orientational ordering transition (continuous change in the tilt) in the LC. Results presented in this paper indicate that, following the capture of the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 56 publications
4
43
1
Order By: Relevance
“…In additional studies, s pecific capture of ligand-functionalized phospholipid vesicles has been reported at LC-aqueous interfaces that were decorated with a monolayer of adsorbed protein (streptavidin or anti-biotin antibody) (Figure 11A) [66]. The specific binding of the vesicles to the proteins was demonstrated to trigger a continuous anchoring transition (continuous change in the tilt) in the LC, which was quantified by measurement of the optical retardance of the LC (Figure 11B-D).…”
Section: Biomolecular Sensing At Lc-aqueous Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional studies, s pecific capture of ligand-functionalized phospholipid vesicles has been reported at LC-aqueous interfaces that were decorated with a monolayer of adsorbed protein (streptavidin or anti-biotin antibody) (Figure 11A) [66]. The specific binding of the vesicles to the proteins was demonstrated to trigger a continuous anchoring transition (continuous change in the tilt) in the LC, which was quantified by measurement of the optical retardance of the LC (Figure 11B-D).…”
Section: Biomolecular Sensing At Lc-aqueous Interfacesmentioning
confidence: 99%
“…(D) Tilt angle of 5CB at the LC-aqueous interfaces corresponding to (B) diamonds and (C) squares. Reproduced with permission [66]. …”
Section: Figurementioning
confidence: 99%
“…reported that these changes in optical appearance result from strong coupling between aliphatic tails of the adsorbed amphiphiles and the mesogens of the LC. The advantages of these adsorbed surfaces make them attractive for a number of potential applications involving more complex interfacial phenomena, such as high-throughput screening of enzymatic activity (Park and Abbott, 2008) and molecular binding events (Hu and Jang, 2012;Hartono et al, 2009;Tan et al, 2012;Liu et al, 2013;Hu and Jang, 2012) through LC reorientations driven by chemical or physical events that perturb the organization of the monolayer interfaces. Enthused by the budding utility of LC materials in biological applications (particularly, reporting biological interactions), in this paper we report progress made in our laboratory toward the design of interfaces of LC materials such that desired interactions are realized between the LC materials and biological systems.…”
Section: Sumyra Sidiq and Santanu Kumar Palmentioning
confidence: 99%
“…32 Briefly, the lipids were dissolved in chloroform (0.5 mL) and dispensed into round bottomed flask. 32 Briefly, the lipids were dissolved in chloroform (0.5 mL) and dispensed into round bottomed flask.…”
Section: Preparation Of Vesiclesmentioning
confidence: 99%